2006
DOI: 10.1212/01.wnl.0000247038.43228.17
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and prognosis of neurologic complications after hematopoietic transplantation

Abstract: Severe neurologic complications after hematopoietic progenitor cell transplantations are common, vary according to the underlying disease and type of transplantation, and are associated with poor survival rates. Better prophylactic protocols and therapy for CNS infections are required in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
58
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 39 publications
1
58
1
Order By: Relevance
“…1,2 However, up to 25% of patients who undergo allo-SCT suffer from more severe neurological complications involving the central nervous system (CNS), frequently infections, which are associated with a poor outcome. [1][2][3][4] The leading causative organisms of CNS infections in patients with malignancies are Toxoplasma gondii and fungi, particularly Aspergillus spp., with typically localized parenchymal manifestations including abscesses or strokes. [4][5][6] Viral CNS infections have less frequently been reported in patients after allo-SCT even though they are the most common type of acute encephalitis in nonimmunocompromised hosts in Western countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 However, up to 25% of patients who undergo allo-SCT suffer from more severe neurological complications involving the central nervous system (CNS), frequently infections, which are associated with a poor outcome. [1][2][3][4] The leading causative organisms of CNS infections in patients with malignancies are Toxoplasma gondii and fungi, particularly Aspergillus spp., with typically localized parenchymal manifestations including abscesses or strokes. [4][5][6] Viral CNS infections have less frequently been reported in patients after allo-SCT even though they are the most common type of acute encephalitis in nonimmunocompromised hosts in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The leading causative organisms of CNS infections in patients with malignancies are Toxoplasma gondii and fungi, particularly Aspergillus spp., with typically localized parenchymal manifestations including abscesses or strokes. [4][5][6] Viral CNS infections have less frequently been reported in patients after allo-SCT even though they are the most common type of acute encephalitis in nonimmunocompromised hosts in Western countries. [7][8][9][10][11] The largest series published to date on viral encephalitis after allo-SCT reported on 23 human herpesvirus-6 (HHV-6) encephalitis patients.…”
Section: Introductionmentioning
confidence: 99%
“…6 Up to 25% of patients develop moderate to severe neurologic complications after allogeneic (allo)HSCT. 7,8 Exposure to neurotoxic medications and disruption of immunity as a part of the HSCT procedure contribute to nervous system complications. 9 In general, CNS infections post-alloHSCT have been associated with higher mortality and rejection rates, whereas long-term neurologic morbidity remains unknown.…”
mentioning
confidence: 99%
“…HHV-6 (subtypes A and B) quantitative, real-time PCR was performed by extracting DNA from a 200-mL aliquot of whole blood or CSF and using primers and probes that amplify and detect a portion of the viral DNA polymerase gene as described previously. 7 The assay is able to differentiate between subtypes A and B based on melt curve analysis. The limit of detection of the PCR assay is 50 genome equivalents per 1.0 mL with a lower limit of the quantifiable range of 250 genome equivalents per 1.0 mL.…”
mentioning
confidence: 99%
“…the authors observed that 9.7% of the children developed neurological complications classified as serious (life-threatening). the main risk factors identified were the main risk status of the underlying disease, mismatched transplantation, previous diagnosis of advanced AML, older age and the presence of grade II or higher graft-versushost-disease (GvhD) 9 . Denier et al described the spectrum and prognosis of neurological complications after hsct in a series of 361 patients.…”
mentioning
confidence: 99%